Analysing the sustainability of Solid Waste Policy in Malaysia using the Ecological Modernization theory - Siti Aisyah Saat,; Noraziah Ali, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
The theory of Ecological Modernisation (EMT) has become one of the dominant sociological theories which attempts to understand and interpret how modern societies are dealing with environmental crises. This paper aims to examine the sustainability of Malaysia’s Solid Waste Management (SWM) programmes from this EMT perspective. It was found that while the EMT requires a national approach in order to effect a more sustainable Solid Waste Management system the current institutional arrangement, managerial process and policy formulation of the SWM in Malaysia has not delivered a cohesive and sustainable national SWM policy. This was caused by factors ranging from the lack of institutional arrangements, policy gaps, and inadequate financial support, to failures in the privatisation process, insufficient manpower and poor understanding of environmental concerns dealing with the whole social complexity of solid waste management . Given such yet-to-be-rectified flaws the application of the EMT to Malaysia’s SWM may be difficult to achieve for now.